MathCity.

org
Merging man and maths

Exercise 4.5 (Solutions)
Calculus and Analytic Geometry, MATHEMATICS 12
Available online @ http://www.mathcity.org, Version: 1.1.0

³ Homogenous 2nd Degree Equation Every homogenous second degree equation ax 2 + 2hxy + by 2 = 0 represents straight lines through the origin. Consider the equations are y = m1 x and y = m2 x ⇒ m1 x − y = 0 and m2 x − y = 0 Taking product ( m1x − y )( m2 x − y ) = 0

⇒ m1m2 x 2 − m1xy − m2 xy + y 2 = 0 ⇒ m1m2 x 2 − ( m1 + m2 ) xy + y 2 = 0 ………. (i) Also we have ax 2 + 2hxy + by 2 = 0 a 2 2h ⇒ x + xy + y 2 = 0 ÷ ing by b b b a 2  2h  ⇒ x −  −  xy + y 2 = 0 b  b  Comparing it with (i ) , we have
a 2h and m1 + m2 = − b b Let θ be the angles between the lines then m1 − m2 tan θ = 1 + m1m2 m1m2 = = =

( m1 − m2 )
1 + m1m2

2

=

2 m12 + m2 − 2m1m2 1 + m1m1

2 m12 + m2 + 2m1m2 − 4m1m2 1 + m1m1

=

( m1 + m2 )

− 4m1m2 1 + m1m1 4h 2 − 4ab b2 b+a b

2

=

a  2h  − b  − 4b   a 1+ b 4 h 2 − ab b+a

2

=

⇒ tan θ =

(

)

4h 2 4a − b b2 a 1+ b

=

2 h 2 − ab tan θ = a+b

Question # 1 10 x 2 − 23xy − 5 y 2 = 0 ………… (i)

⇒ 10 x 2 − 25xy + 2 xy − 5 y 2 = 0 ⇒ 5 x ( 2 x − 5 y ) + y ( 2 x − 5 y ) = 0 ⇒ ( 2 x − 5 y )( 5 x + y ) = 0 ⇒ 2 x − 5 y = 0 and 5 x + y = 0 are the required lines. Comparing eq. (i) with ax 2 + 2hxy + by 2 = 0

FSC-II / Ex. 4.5 - 2

So

a = 10

,

2h = −23 ⇒ h = −

Let θ be angle between lines then 2 h 2 − ab tan θ = a+b

23 2

,

b = −5

 23  529 2  −  − (10)(−5) 2 + 50  2  4 = = 10 − 5 5 2 27 2 729 27 2 4 = = = 5 5 5  27  ⇒ θ = tan −1   = 79o31′  5  Hence acute angle between the lines = 79o31′

2

( )

Question # 2 & 3

Do yourself as above

Question # 4 2 x 2 + 3xy − 5 y 2 = 0 ………… (i) ⇒ 2 x 2 + 5 xy − 2 xy − 5 y 2 = 0 ⇒ x ( 2 x + 5 y ) − y ( 2x + 5 y ) = 0 ⇒ ( 2 x + 5 y )( x − y ) = 0 ⇒ 2 x + 5 y = 0 and x − y = 0 are the required lines. Comparing eq. (i) with ax 2 + 2hxy + by 2 = 0 3 ⇒ a = 2 , 2h = 3 ⇒ h = , b = −5 2 Let θ be angle between lines then 2 h 2 − ab tan θ = a+b 3 9 2   − (2)(−5) 2 + 10 2 4 = = 2−5 −3 2 7 2 49 7 2 4 = − = − = − 3 3 3 7 − tan θ = 3 7 tan (180 − θ ) = Q tan(180 − θ ) = − tan θ 3 7 180 − θ = tan −1   ⇒ 180 − θ = 66o 48′ 3 θ = 180 − 66o 48′ = 113o12′
2

( )

⇒ ⇒ ⇒

⇒ Hence acute angle between the lines
Question # 5

= 180 − 113o12′ = 66o 48′

Do yourself as above

FSC-II / Ex. 4.5 - 3

Question # 6 x 2 + 2 xy sec α + y 2 = 0 ………. (i)

÷ ing by y 2
x 2 2 xy secα y 2 + + 2 = 0 y2 y2 y x x  + 2secα  y  + 1 = 0 y   x This is quadric equation in with a = 1 , b = 2secα , c = 1 y −2sec α ± x = y  ⇒  
2

( 2secα )2 − 4(1)(1)
2(1) = −2sec α ± 4 sec 2 α − 1 2

−2sec α ± 4sec 2 α − 4 = 2(1) −2sec α ± 4 tan 2 α 2 −2sec α ± 2 tan α = 2 = x = − sec α ± tan α y 1 sin α = − ± = cos α cosθ x −1 + sin α ⇒ = and y cos α ⇒ x cos α = ( −1 + sin α ) y ⇒

(

)

Q 1 + tan 2 α = sec 2 α

−1 ± sin α cos α x −1 − sin α = y cos α and x cos α = ( −1 − sin α ) y ⇒ x cos α − ( −1 + sin α ) y = 0 and x cos α − ( −1 − sin α ) y = 0 ⇒ x cos α + (1 − sin α ) y = 0 and x cos α + (1 + sin α ) y = 0 are required equations of lines. Now comparing (i) with ax 2 + 2hxy + by 2 = 0 a = 1 , 2h = 2secα ⇒ h = secα , b = 1b If θ is angle between lines then
2 h 2 − ab a+b 2 sec 2 α − (1)(1) 2 sec 2 α − 1 = = 1+1 2 ⇒ tan θ = tan α ⇒ θ = α tan θ = Question # 7 x 2 − 2 xy tan α − y 2 = 0 Given: Suppose m1 and m2 are slopes of given lines then 2h m1 + m2 = − b − 2 tan α = − −1 ⇒ m1 + m2 = − 2 tan α a 1 & m1m2 = = ⇒ m1m2 = − 1 b −1

=

tan 2 α

a =1 , 2h = −2 tan α ⇒ h = − tan α b = −1

FSC-II / Ex. 4.5 - 4

Now slopes of lines ⊥ ar to given lines are − 1 x & m1 ⇒ m1 y = − x & ⇒ x + m1 y = 0 & Their joint equation: ( x + m1 y )( x + m2 y ) y = − y = −

1 1 and − , then their equations are m1 m2 (Passing through origin)

1 x m2 m2 y = − x x + m2 y = 0

⇒ x 2 + ( m1 + m2 ) xy + m1m2 y 2 = 0 ⇒ x 2 + ( −2 tan α ) xy + (−1) y 2 = 0 ⇒ x 2 − 2 xy tan α − y 2 = 0

= 0

Question # 8 Given: ax 2 + 2hxy + by 2 = 0 Suppose m1 and m2 are slopes of given lines then 2h a m1 + m2 = − & m1m2 = b b 1 1 and − , then their equations are Now slopes of lines ⊥ ar to given lines are − m1 m2 1 1 & (Passing through origin) y = − x y = − x m1 m2 ⇒ m1 y = − x & m2 y = − x ⇒ x + m1 y = 0 & x + m2 y = 0 Their joint equation: ( x + m1 y )( x + m2 y ) = 0

⇒ x 2 + ( m1 + m2 ) xy + m1m2 y 2 = 0
 2h  a ⇒ x 2 +  −  xy +   y 2 = 0  b  b ⇒ bx 2 − 2hxy + ay 2 = 0

Question # 9 10 x 2 − xy − 21y 2 = 0

,

x + y +1= 0

⇒ 10 x 2 − 15 xy + 14 xy − 21y 2 = 0 ⇒ 5x ( 2 x − 3 y ) + 7 y ( 2 x − 3 y ) = 0 ⇒ ( 2 x − 3 y )( 5 x + 7 y ) = 0 ⇒ 2 x − 3 y = 0 or 5x + 7 y = 0 So we have equation of lines l1 : 2 x − 3 y = 0 ……..… (i) l2 : 5 x + 7 y = 0 ………. (ii) l3 : x + y + 1 = 0 ……… (iii) Now do yourself as Q # 14 (Ex. 4.4)
Error Analyst Muhammad Tayyab Riaz (2009-10) Pakistan International School Al-Khobar, Saudi Arabia.

Sign up to vote on this title
UsefulNot useful